CLINICAL CASE OF REMOVING SUPRACEREBELLAR TUMOR OF POSTERIOR CRANIAL FOSSA. (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Medulloblastoma (MB) is an embryonal tumor originating from the midlinecerebellum with the potential for leptomeningeal spread [1]. MBs account for 61.9% of all posterior fossa embryonal tumors and account for 14.3% of childhood mortality [2–5]. Early diagnosis of MB is difficult due to the initial nonspecific clinical symptoms, especially in very young children. The most common signs of posterior fossa space-occupying lesions are symptoms of intracranial hypertension, visual and cerebellar disturbances, as well as seizures, behavioral changes, and cranial nerve deficits [6–9]